2022
DOI: 10.1155/2022/6033989
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Percutaneous Spinal Endoscopy versus Traditional Open Surgery for Lumbar Disc Herniation: Systematic Review and Meta-Analysis

Abstract: Objective. Systematic analysis of the incidence of percutaneous spinal endoscopic technique and traditional open surgery for lumbar disc herniation. Methods. A randomized controlled trial (RCT) and cohort study on complications related to traditional open surgery was searched on the MEDLINE, Cochrane Library, PubMed, Web of Science, Chinese journal full-text database (CNKI), Wanfang, and Embase database. Language is not limited. The quality of each study was evaluated, various complications were compiled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…MISS techniques have rapidly improved over the past 2 decades, and one of the most advanced MISS techniques for patients with lumbar disc herniation is TELD [ 12 ]. TELD minimizes damage to surrounding structures and does not require general anesthesia [ 12 , 34 ]. Several authors have reported that TELD is superior to conventional surgery, including microscopic discectomy, in terms of outcomes and complication rates [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MISS techniques have rapidly improved over the past 2 decades, and one of the most advanced MISS techniques for patients with lumbar disc herniation is TELD [ 12 ]. TELD minimizes damage to surrounding structures and does not require general anesthesia [ 12 , 34 ]. Several authors have reported that TELD is superior to conventional surgery, including microscopic discectomy, in terms of outcomes and complication rates [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TELD minimizes damage to surrounding structures and does not require general anesthesia [ 12 , 34 ]. Several authors have reported that TELD is superior to conventional surgery, including microscopic discectomy, in terms of outcomes and complication rates [ 34 , 35 ]. Based on this concept, many authors have suggested that MISS might be more beneficial than conventional surgery in the elderly, and full endoscopic surgery could be applied safely in elderly patients [ 7 , 34 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the weakening of the muscle strength of the lumbar back may lead to the occurrence of lumbar instability. [20,21] To further improve the clinical effect of surgery, spine surgery has entered the era of minimally invasive surgery under the continuous research of spine surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the need to peel off the paravertebral muscle in spinal surgery, the distal nerve of the muscle is innervated, which may lead to intractable back pain after surgery. At the same time, the weakening of the muscles in the lower back will cause instability in the lumbar spine [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%